Plasma & subcutaneous tissue pharmacokinetics of piperacillin in a large cohort of critically ill patients with sepsis - Abdul Aziz, Mohd. Hafiz; Udy, Andrew A.; Wallis, Steven C.; Roberts, Michael S.; Lipman, Jeffrey; Roberts, Jason A. (2014)
Critically ill patients with sepsis can develop profound pathophysiological changes that may alter antibiotic pharmacokinetics (PK) and produce sub-therapeutic concentrations at the sites of infection leading to therapeutic failure. We aimed to describe the plasma PK of piperacillin and its associated penetration into interstitial fluid (ISF) of subcutaneous tissue. We also sought to describe risk factors for not achieving PK/pharmacodynamic (PK/PD) targets in critically ill patients with sepsis.